THE ROLE OF WOMEN'S ENTREPRENEURSHIP IN SOCIAL WELFARE AND ECONOMIC DEVELOPMENT (American Journal of Research in Humanities and Social Sciences, 2025)
This study examines the role of women’s entrepreneurship in social welfare and economic development. Women’s entrepreneurship contributes to job creation, innovation, market competitiveness, and economic stability while promoting gender equality and social well-being. The research highlights the impact of digitalization on female entrepreneurship, particularly in developing countries like Uzbekistan. Despite government efforts to support women-led businesses, digitalization has yet to significantly transform their entrepreneurial activities. The study suggests that fostering innovative women-owned enterprises can enhance sustainable economic growth and social progress.